2022
DOI: 10.1021/acs.jced.2c00156
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of Phosphonocarboxylates in Aqueous Medium: An Experimental and Theoretical Investigation

Abstract: Phosphonates and carboxylates are two primitive functional groups omnipresent in nature, and they act as good chelators for metal ion binding. These two functional groups are always associated with dissociable protons in their acidic forms. Thus, their interactions are associated with protonation/deprotonation mechanisms. The present study was aimed at determining the thermodynamic parameters (log K P/pK a, ΔG P, ΔH P, and ΔS P) for the protonation of three aliphatic phosphonocarboxylates, namely, phosphonofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Upon complexations, extractants with dissociable protons are prone to protonation and deprotonation, and thus, a change in the hydrogen ion concentration (pH) is a good indicator of complexation progress. In the present study, the sequential progress of complexation is probed by adding a concentrated ligand solution into a fixed concentration of a metal solution and monitoring the pH after each addition of the ligand. Potentiometric data were analyzed by Hyperquad program , to deduce the species present along with stability for complex formation during the course of the reaction. Speciation plots (Figure ) showed that Th­(IV) forms ML i ( i = 1–4) complexes with both extractants.…”
Section: Resultsmentioning
confidence: 99%
“…Upon complexations, extractants with dissociable protons are prone to protonation and deprotonation, and thus, a change in the hydrogen ion concentration (pH) is a good indicator of complexation progress. In the present study, the sequential progress of complexation is probed by adding a concentrated ligand solution into a fixed concentration of a metal solution and monitoring the pH after each addition of the ligand. Potentiometric data were analyzed by Hyperquad program , to deduce the species present along with stability for complex formation during the course of the reaction. Speciation plots (Figure ) showed that Th­(IV) forms ML i ( i = 1–4) complexes with both extractants.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical nature of the participating ligand and the geometry arrived by its coordination on the equatorial plane has phenomenal effects on the intensities and positions of electronic transitions of the uranyl ion in the range of 380–480 nm arising from vibronic perturbed electronic transitions. , The protonation process is an inseparable mechanism while studying the complexation phenomenon, especially with the protonated/deprotonated ligands; and the protonation thermodynamic data are a prerequisite to obtain the complexation thermodynamics data. The present studies utilized the protonation data from our previous work . The present studies involve the titration mode of absorption measurement, in which to a fixed volume of uranyl solution, the ligand solutions were added in increments and the spectra were collected for each addition of the ligand in the 380–480 nm range with a 1 nm interval for data collection.…”
Section: Resultsmentioning
confidence: 99%
“…The present studies utilized the protonation data from our previous work. 72 The present studies involve the titration mode of absorption measurement, in which to a fixed volume of uranyl solution, the ligand solutions were added in increments and the spectra were collected for each addition of the ligand in the 380−480 nm range with a 1 nm interval for data collection. Uranyl showed a red shift in absorption spectra on ligand addition with an increase in the absorption intensities too upon interaction with all phosphonocarboxylates (Figure 1A).…”
Section: Molecular Speciationmentioning
confidence: 99%